Christians of the patristic period in relation to nature - Szram, Mariusz; Wysocki, Marcin (Studia patristica, 2024)
"This volume in the Studia Patristica series consists of 34 articles devoted to humanity's relation to nature and creation as found in the patristic period, and is the result of the fourth International Patristic Conference, which was held at the John Paul II Catholic University of Lublin (Lublin, Poland) on October 18-20, 2022. The articles presented in this volume cover the entire patristic period and discuss various issues related to nature, creation and the Christian's relation to the created world as it was presented in the works of, inter alia, Theophilus of Antioch, Irenaeus of Lyons, Philo, Clement, Origen of Alexandria, Tertullian, Cyprian, Lactantius, Victorinus, Tyconius, Evagrius, Epiphanius of Salamis, Basil of Caesarea, Theodoret of Cyrrhus, Nemesius of Emesa, Philastrius of Brescia, Jerome, Augustine, Paulinus of Nola, John Chrysostom, Commodianus, Gregory of Tours and Maximus the Confessor. The articles presented in the volume allow us to know and to understand better the intuitions and interpretations of early Christian writers concerning the relation of human beings to the surrounding natural world created by God; to consider what models and approaches to the animate and inanimate natural world modern people can take over from the Christians of the patristic period; to what extent they are valid today; to what extent they were part of the philosophical and theological context of their time; and in what respects they were original in relation to pagan views."--